Desain Microcomputer Cloud Computing for Informatics Study Program at LIA University Based on Local Area Network (LAN) - Ariya Pannadhitthana Candra; Murniasih, Intan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2026)
Digital transformation in higher education increasingly requires information technology infrastructure that is efficient, flexible, secure, and sustainable. Cloud computing has emerged as a strategic solution by enabling scalable resources, centralized management, and service standardization effectively. However, public cloud adoption in academic institutions frequently encounters constraints, including recurring operational costs, data security and sovereignty risks, regulatory concerns, and strong dependence on reliable internet connectivity. These issues are particularly salient for instructional laboratories that demand continuous access, predictable performance, and institutional control. This study aims to design and implement a Local Area Network (LAN)-based cloud computing system using a microcomputer as the primary server within the Informatics Study Program at LIA University. The research employs a research and development (R&D) methodology comprising needs analysis, system architecture design, implementation, and functional as well as performance testing. An open-source virtualization platform is deployed to deliver Infrastructure as a Service (IaaS) and Software as a Service (SaaS) in a private cloud environment. The results demonstrate that the proposed LAN-based local cloud provides centralized computing and storage services with low latency, high stability, and efficient utilization.